(untitled) (Colloquia Comparativa Litterarum, 2025)
In the 1970s, novelist and literary theory scholar Hans Robert Jauss developed the modern concept of the “aesthetics of reception” or “reception‐aesthetics” (German Rezeptionsästhetik) of a literary work. This notion can be applied to a translation process that aims at finding the strategies for an optimal aesthetic reception. In this article I shall examine the translation strategies of Barbara Wanders de Vincenz who translated into French the ethnographical studies on the traditional Christmas celebrations in the Carpathians. They were written by her father, Stanisław Vincenz, a 20th century Polish writer, and were included in his masterpiece Na wysokiej Połoninie (On the High Uplands).